ЎҚУВ ТОПШИРИҚЛАРИ МУТАХАССИСЛИК ФАНЛАРНИ ЎҚИТИШНИНГ САМАРАДОРЛИГИНИ ТАЪМИНЛАШ ОМИЛИ СИФАТИДА - Курбаниязова, З.К. (SCIENCE and SOCIETY, 2024)
The article analyzes the role of specialized subjects in the methodical training of future primary school teachers, the issues of appropriate application of educational tasks in improving the teaching methodology of specialized subjects.